2013
DOI: 10.1519/jsc.0b013e31829992b0
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison Between Sprint Start, Sled Pulling, and Selected Squat-Type Exercises

Abstract: Okkonen, Olli 2012. Biomechanical comparison between sprint start, sled-pulling and selected squat type exercises. Department of Biology of Physical Activity, University of Jyväskylä.Master's Thesis in Science of Sport Coaching and Fitness Testing. 69 pp.The purpose of the present study was to compare kinetics, kinematics and muscle activity between sprint start, sled-pulling and selected squat type exercises and also to examine how different exercises and variables correlate with the performance time of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“… Maulder et al (2008) also agreed that a load of approximately 10% Bm may not provide a sufficient training stimulus in a block start action. The use of higher loads for sled towing may provide training stimulus for young athletes, when also considering the increase in muscular activity in sled towing ( Okkonen and Häkkinen, 2013 ). Cormie et al (2011b) suggested the use of an optimal load would provide an effective stimulus to elicit increases in maximal power output.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Maulder et al (2008) also agreed that a load of approximately 10% Bm may not provide a sufficient training stimulus in a block start action. The use of higher loads for sled towing may provide training stimulus for young athletes, when also considering the increase in muscular activity in sled towing ( Okkonen and Häkkinen, 2013 ). Cormie et al (2011b) suggested the use of an optimal load would provide an effective stimulus to elicit increases in maximal power output.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, athletes using sled towing should imitate the range of motion, body position, muscle activation time, and sprint velocity near the running speeds used in competition ( Alcaraz et al, 2009 ; Kanehisa and Miyashita, 1983 ; Kaneko et al, 1983 ; Murray et al, 2005 ). Furthermore, Okkonen and Häkkinen (2013) found that resisted sprint exercises produce greater muscular activation when compared to free sprinting. Additionally, this training method increases force output ( Alcaraz et al, 2014 ; Harrison and Bourke, 2008), stride length in the acceleration phase in team sport athletes ( Kawamori et al, 2014a ), the maximum velocity phase in sprinters ( Alcaraz et al, 2014 ), and stride frequency in the acceleration and maximum speed phase ( Clark et al, 2010 ; Zafeiridis et al, 2005 ).…”
Section: Introductionmentioning
confidence: 98%
“…These findings suggest that the hip extensor kinetics is a key contributor to high block-induced power. This leg extension motion during the block start phase is similar to the double-legged squat motion [ 10 ]. Biomechanical analysis of the squatting motion has revealed that lengthening the mediolateral distance between feet (140% of shoulder width) contributes to stronger isometric contractions in lower limb muscles [ 11 ].…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, the recommended intervention for targeting a weak quad muscle would be the WP task, because it is the most beneficial activity for training both strength and endurance due to the increased muscle activation as well as the later timing in maximal contraction. Studies showed (Maddigan M, Button D, Behm D., 2014& Okkonen, O. & Häkkinen, K. 2013) similar activation of the Quads muscle pushing a sled compared to a squat manoeuvre and squat type exercises.…”
Section: Discussionmentioning
confidence: 99%
“…& Häkkinen, K. 2013) similar activation of the Quads muscle pushing a sled compared to a squat manoeuvre and squat type exercises. In addition, it has been found in multiple studies (Okkonen, O. & Häkkinen, K., 2013& Fry, A.C., Smith, J.C., & Schilling, B.K., 2003 that performing a squat without proper form can increase stress at the knee joint.…”
Section: Discussionmentioning
confidence: 99%